2018
DOI: 10.1371/journal.pone.0195276
|View full text |Cite
|
Sign up to set email alerts
|

Effects of repetitive transcranial magnetic stimulation and trans-spinal direct current stimulation associated with treadmill exercise in spinal cord and cortical excitability of healthy subjects: A triple-blind, randomized and sham-controlled study

Abstract: Repetitive transcranial magnetic stimulation (rTMS) over motor cortex and trans-spinal direct current stimulation (tsDCS) modulate corticospinal circuits in healthy and injured subjects. However, their associated effects with physical exercise is still not defined. This study aimed to investigate the effect of three different settings of rTMS and tsDCS combined with treadmill exercise on spinal cord and cortical excitability of healthy subjects. We performed a triple blind, randomized, sham-controlled crossove… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
43
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(44 citation statements)
references
References 62 publications
1
43
0
Order By: Relevance
“…This finding, together with the absence of group differences at the This study found that anodal-tsDCS prolonged the duration of H-reflex down-regulation following training relative to sham-tsDCS. Our data confirm prior studies showing that exercise such as BLT leads to transient down-regulation of the H reflex (77,78). We have shown that tsDCS can prolong the period of exercise-induced down-regulation of the H reflex, which may contribute to the behavioral gains during BLT (79).…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…This finding, together with the absence of group differences at the This study found that anodal-tsDCS prolonged the duration of H-reflex down-regulation following training relative to sham-tsDCS. Our data confirm prior studies showing that exercise such as BLT leads to transient down-regulation of the H reflex (77,78). We have shown that tsDCS can prolong the period of exercise-induced down-regulation of the H reflex, which may contribute to the behavioral gains during BLT (79).…”
Section: Discussionsupporting
confidence: 90%
“…From a kinematic point of view, changes in step length related to improved confidence with training was a likely contributor to speed improvements (64,(80)(81)(82). From a mechanistic angle, previously reported tsDCS influences on H-reflex modulation (77,78,83) impacts speed and symmetry of locomotion and modulates H-reflex post-activation (20), central nociceptive signal transmission (15,21) possibly contributing to speed improvements as well. Alternatively, tsDCS could have modified cortical plasticity underlying motor learning through modulation of somatosensory and motor (16,21) evoked potentials as well as interhemisperic inhibition (22,23).…”
Section: Discussionmentioning
confidence: 87%
See 1 more Smart Citation
“…However, we believe the lack of a sham-control condition does not undermine the main findings. Prior work that has included a sham-control arm, but did not investigate genetic moderators of rTMS response, demonstrates that cortical excitability changes in the expected direction following real, but not sham, stimulation (e.g., Todd et al, 2009;Albuquerque et al, 2018), suggesting that the effects of rTMS on MEP amplitudes are not due to order effects (i.e., prior elicitation of MEPs via single-pulse TMS) and/or placebo effects. Regarding the BDNF polymorphism, studies have shown that MEPs decrease to a greater extent for homozygous Val carriers when compared to Val66Met carriers in the absence of repetitive NIBS protocols (e.g., motor learning tasks; e.g., Kleim et al, 2006); however, the current study did not include a voluntary motor (learning) component.…”
Section: Discussionmentioning
confidence: 99%
“…Accordingly, it appears that the more efficient is the energy-generating capacity of these mitochondria, the higher is the resistance to mechano-energetic lesions at the terminals of these sensory neurons. It is noteworthy that proprioceptive training not only enhances the neuro-energetic capacity and plasticity of the proprioceptive system at the terminals of the peripheral sensory nerves, but likely at spinal and supraspinal levels as well [ 30 , 139 , 140 , 141 ]. It is important to emphasize the findings of Dargo et al [ 138 ] again that more training or more added components to the programs were not leading to better outcome.…”
Section: Acl Injury Prevention: Neuromuscular and Proprioceptive Trainingmentioning
confidence: 99%